Closing in on Mechanisms of Open Neural Tube Defects. Issue 7 (July 2020) - Lee, Sangmoon; Gleeson, Joseph G.
Abstract : Neural tube defects (NTDs) represent a failure of the neural plate to complete the developmental transition to a neural tube. NTDs are the most common birth anomaly of the CNS. Following mandatory folic acid fortification of dietary grains, a dramatic reduction in the incidence of NTDs was observed in areas where the policy was implemented, yet the genetic drivers of NTDs in humans, and the mechanisms by which folic acid prevents disease, remain disputed. Here, we discuss current understanding of human NTD genetics, recent advances regarding potential mechanisms by which folic acid might modify risk through effects on the epigenome and transcriptome, and new approaches to study refined phenotypes for a greater appreciation of the developmental and genetic causes of NTDs. Highlights: Neural tube defects (NTDs) are the most common birth anomaly of the CNS. They result from a failure of the neural plate to complete the developmental transition to a neural tube. Mandatory folic acid (FA) supplementation of dietary grains led to a significant decrease in the incidence of NTDs, but the mechanisms involved remain disputed. NTD is a relatively common phenotype in mouse knockouts, showing both simple and complex inheritance, as well as responses to folate, yet few of the genes identified in mouse models have been established as causes in human NTDs. Candidate gene approaches in human studies support a role for Wnt/planar cell polarity, cilia, Sonic Hedgehog (Shh), and bone morphogenetic protein (BMP) signaling factors in NTD risk. Whole-genome sequencing, as opposed to SNP genotyping or candidate gene resequencing, allows for detection of most coding, noncoding, and structural variants, including rare, common, de novo, and somatic variants. Recently, there have been collaborative efforts to assemble larger cohorts of phenotypically diverse patients from diverse ethnic groups, both prior to and after FA fortification, for comprehensive risk assessment.